The inotropic and arrhythmogenic effects of acutely increased late INa are associated with elevated ROS but not oxidation of PKARIα - Gissibl, Theresa; Stengel, Laura; Tarnowski, Daniel; Maier, Lars S.; Wagner, Stefan; Feder, Anna-Lena; Sag, Can Martin (Frontiers in Cardiovascular Medicine, 2024)
Background Acute stimulation of the late sodium current (INaL) as pharmacologically induced by Anemonia toxin II (ATX-II) results in Na+-dependent Ca2+ overload and enhanced formation of reactive oxygen species (ROS). This is accompanied by an acute increase in the amplitude of the systolic Ca2+ transient. Ca2+ transient amplitude is determined by L-type Ca2+-mediated transsarcolemmal Ca2+ influx (ICa) into the cytosol and by systolic Ca2+ release from the sarcoplasmic reticulum (SR). Type-1 protein kinase A (PKARIα) becomes activated upon increased ROS and is capable of stimulating ICa, thereby sustaining the amplitude of the systolic Ca2+ transient upon oxidative stress. Objectives We aimed to investigate whether the increase of the systolic Ca2+ transient as acutely induced by INaL (by ATX-II) may involve stimulation of ICa through oxidized PKARIα. Methods We used a transgenic mouse model in which PKARIα was made resistant to oxidative activation by homozygous knock-in replacement of redox-sensitive Cysteine 17 with Serine within the regulatory subunits of PKARIα (KI). ATX-II (at 1 nmol/L) was used to acutely enhance INaL in freshly isolated ventricular myocytes from KI and wild-type (WT) control mice. Epifluorescence and confocal imaging were used to assess intracellular Ca2+ handling and ROS formation. A ruptured-patch whole-cell voltage-clamp was used to measure INaL and ICa. The impact of acutely enhanced INaL on RIα dimer formation and PKA target structures was studied using Western blot analysis. Results ATX-II increased INaL to a similar extent in KI and WT cells, which was associated with significant cytosolic and mitochondrial ROS formation in both genotypes. Acutely activated Ca2+ handling in terms of increased Ca2+ transient amplitudes and elevated SR Ca2+ load was equally present in KI and WT cells. Likewise, cellular arrhythmias as approximated by non-triggered Ca2+ elevations during Ca2+ transient decay and by diastolic SR Ca2+-spark frequency occurred in a comparable manner in both genotypes. Most importantly and in contrast to our initial hypothesis, ATX-II did not alter the magnitude or inactivation kinetics of ICa in neither WT nor KI cells and did not result in PKARIα dimerization (i.e., oxidation) despite a clear prooxidant intracellular environment. Conclusions The inotropic and arrhythmogenic effects of acutely increased INaL are associated with elevated ROS, but do not involve oxidation of PKARIα.